PENGEMBANGAN BAHAN AJAR KENDARAANKU DALAM PEMBEALAJARAN STEAM ANAK USIA DINI UNTUK KELOMPOK A DI RA INSANI DAMPIT-MALANG - Assabillah, Khurrun Ainiyah (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2024)
The Early childhood STEAM learning through my vehicle teaching materials. The purpose of this research is to describe my vehicle teaching materials and to describe the results of developing my vehicle teaching materials in STEAM learning at RA Bina Insani Dampit. This type of research uses research and development (R&D) methods, namely methods that produce a product and then test the effectiveness of the product. This research develops teaching material media in STEAM learning for early childhood. The research results developed through the media of my vehicle teaching materials were designed using the Microsoft Word and Canva applications. In media expert validation 96.25%. Material expert validation obtained a percentage of 95.83%. The results of the small group trials were 90.55%, while the results of the large group trials were 99.75%. The teaching material media used presented material with the sub-theme of land vehicles. So, my vehicle teaching material media has many benefits that have a positive impact on learning in a relevant form and serve as a guide for educators to create collaboration in making thematic teaching materials to improve aspects of children's development through a more innovative STEAM approach.